Factors Affecting Household’s Intention to Save Power: The Case of Chau Thanh District – Vietnam - Son, Nguyen Truong; Le, Doan Hong; Nghiem, Dong Luu; Giang, Doan Quynh (International Journal of Energy Economics and Policy, 2022)
Saving electricity is a matter of concern now and in the future when electricity consumption tends to increase, greatly affecting national energy security. Synthesizing research and theories related to the topic, the author's team has conducted a survey of 305 households in Chau Thanh district, Kien Giang province, Vietnam to assess the influencing factors and the extent to which they are affected. The influence of factors on the intention to save electricity. The results of the regression analysis show that the factors in the research model explain 59.4% of the change in the intention to save electricity of households in the study area. The study also shows the level of impact of factors on the intention to save electricity of households in order of decreasing impact level. Based on the research results, the authors will make some feasible and reasonable recommendations for local and national electricity saving policies, as a basis for different types of electricity consumption and other similar service for reference. Survey data were analyzed using SPSS version 20.0, including descriptive and inferential statistics. Research results show that most of the variables have a positive correlation with the intention to save electricity of people in the area.